Therapeutic trajectories of families with rare diseases in Chile from the perspectives of patients, carers, and healthcare workers: a qualitative study - CABIESES VALDES, BALTICA BEATRIZ; OBACH KING, ALEXANDRA ALICE; Antonia Roberts; REPETTO LISBOA, MARIA GABRIELA (Springer Science and Business Media LLC, 2025)
Background Rare diseases are conditions that have a low prevalence in the population and a high disease burden and are often chronic and progressive. International evidence concerning the experience of people and families living with rare diseases is scarce, leading to late and erroneous diagnoses, as well as non-specific treatments. This study explored the therapeutic trajectories of people and families living with rare diseases within Chile’s public and private healthcare systems from the perspective of patients, caregivers, and medical teams, including the initial symptoms, first consultation, testing, diagnosis, treatment, and follow-up. Methods A qualitative exploratory study was conducted through multiple case studies. Sixty participants were interviewed in person and/or virtually: patients (n = 16), caregivers (n = 22), healthcare workers (n = 20), and two patient organisation leaders. The material was analysed using thematic analysis. The project was approved by the Scientific Ethics Committee of Facultad de Medicina Clínica Alemana, Universidad del Desarrollo. Results After similar initial symptoms and first consultation, three main types of trajectories were identified: (i) the path taken by those who reach a diagnosis for a disease that has specific treatment available; (ii) the journey of those who reach a diagnosis for their health condition, but their disease does not have a specific treatment available; and (iii) the trajectory of those who have not reached a diagnosis and receive symptomatic treatments for symptoms. Conclusions The therapeutic trajectories of patients with rare symptoms are similar in terms of initial symptoms and first consultation. However, their paths diverge at the diagnostic stage, with diverse experiences related to these journeys, largely based on having a diagnosis and whether there is a specific treatment. Rare conditions in Chile requires further attention and urgent action that considers those who live with them and their families.
Keywords: adult; caregivers; chile; female; health personnel; humans; male; middle aged; qualitative research; rare diseases; adolescent; adult; article; caregiver; chile; consultation; disease burden; exploratory research; family; female; follow up; health care personnel; health care system; human; interview; major clinical study; male; mental health care; mental health service; perception; prevalence; public health; qualitative analysis; qualitative research; rare disease; thematic analysis; therapeutic trajectories; chile; middle aged; psychology; rare disease; chile; healthcare systems; perceptions and experiences; qualitative analysis; rare diseases; therapeutic trajectories